Tourism Geography Learning Process in 21st Century Competencies Efforts for Geography Education Students - Zulkarnain, Zulkarnain; Pargito, Pargito; Salsabilla, Annisa (Jurnal Pendidikan Progresif, 2021)
Tourism Geography Learning Process in 21st Century Competencies Effort for Geography Education Students. Objectives: This research aims to find the content of 21st century competencies in the learning process of tourism geography subject. Methods: It is a qualitative research and data collection techniques are observation, interview, and documentation. The subjects are 14 students who were divided into students from villages and cities.. Findings: The results showed that the learning process from the curriculum aspect and the tourism geography learning process has formed the character of collaboration, creativity, and critical thinking, but the content of communication competence has not been maximally formed. In addition, students from rural areas tend to have better cooperative and social care characteristics than urban students. Conclusion: The tourism geography learning process has formed the character of students in accordance with 21st century competencies, namely collaboration, creativity, and critical thinking, but personality factors and habits from the area of origin also influence the development of student character during college.Keywords: 21st century education, student character, character education.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202105